Ultrastructure Study of Follicular Cells in Hypothyroidism-induced Rats Treated with Insulin-like Growth Factor-1 and Some Minerals - Hasoon, Douaa S.; Hadi, Maysaa A.; Bahrami, Ali M.; Zaidan, Haider K. (Iraqi Journal of Science, 2025)
The objective of this study is to examine the impact of the administration of levothyroxine (T4), insulin-like growth factor-1, zinc, selenium, and vitamin B12 for 2 months to methimazole-induced hypothyroid adult male Wistar albino eight-week-old rats weighing 180–250 gm were bought from the Ilam Lab of Animals and n=8 was for each group. The thyroid hormones, thyroid stimulating hormone, and ultrastructure of follicular cells by transmission electron microscope were compared between the control group and 7 groups of hypothyroid rats treated with T4, insulin-like growth factor-1, T4 + insulin-like growth factor-1, T4+zinc, T4+selenium, T4+ selenium, and T4+zinc +selenium + vitamin B12, respectively. The hypothyroid rats displayed a significant rise (P≤0.05) in thyroid-stimulating hormone levels compared with the control group, with significant differences verified in the treatment groups treated with GF1 in comparison to the hypothyroid group, while a significant difference in TSH levels was observed in hypothyroid rats administrated with T4+Zn, T4+Vit. B12, and T4+Zn+Se+Vit. B12 compared to those groups that were hypothyroid and control. Moreover, the methimazole-induced hypothyroidism group had ultrastructural degenerative alterations in both the cytoplasm and nucleus of the rat's thyroid follicular cells, while the treating groups had regeneration in the thyroid hormones, thyroid stimulating hormone, and ultrastructure of the follicular cells. In conclusion, both T4 + insulin-like growth factor-1 and T4 + zinc + selenium + vitamin B12 treatment groups produced a considerable enhancement in the thyroid follicular cell's ultrastructure and appropriate for application in hypothyroidism treatment.